The Inheritance of Property and the Position of Sons in Accordance with the Matrilinial System in the Minangkabau Indigenous People and Its Relationship with the Rules of al-Adah Muhakkamah - Syafira Syafira; Ahyat Habibi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Inheritance according to Islamic law regulates the principles of inheritance, terms and pillars of inheritance, heirs, and arrangements regarding the amount of inheritance received by heirs. Fundamentally related to inheritance matters have been regulated in Islamic law, but in reality not all Muslims share the inheritance with reference to the provisions regarding the distribution of inheritance in the fiqh Mawaris. Customs and habits that grow in a person's social environment, become the reason that person is bound by a law. Such as Minangkabau customary inheritance law is one area that still uses customary law as a reference for the division of inheritance. The matrilineal inheritance distribution system makes the position of the woman's party higher in terms of inheritance portion than the male's. Whereas in the syar'i texts and in what has been taught the portion of men is twice as large as women. The acceptance of custom or urf as a proposition is a form of Islamic law's attention to the customs that apply in society. Meanwhile, related to the rule of al-adah muhakkamah with custom or urf there is a dispute with the syar'i text. This journal writing method uses a normative juridical type of writing, which is a research method that uses studies and explanations in laws and materials that contain law to regulate the legal issues studied.